The Relationship between Self-efficacy and Motivation to Prevent Complications with Degree of Hypertension in the Elderly in the Working Area of the Puskesmas Mukomuko City Year 2022 - Samidah, Ida; Handayani, Tita Septi; Lestari, Merry (Universitas Dehasen Bengkulu, 2023)
Hypertension causes high morbidity (illness) and mortality (death). In general, there are two ways to control blood pressure so that it remains stable, namely pharmacotherapy and lifestyle changes. The successful management of hypertension depends on the patient's own motivation and self-awareness to carry out self-care management designed to control symptoms and avoid complications. The purpose of this study is the relationship between self-efficacy and motivation to prevent complications with the degree of hypertension in the elderly in the working area of ​​the Mukomuko City Health Center in 2022. The design of this study used a descriptive corelational cross sectional method. Sampling used purposive sampling technique, the number of respondents was 54 elderly people with a diagnosis of hypertension. The independent variables in this study are self-efficacy and motivation and the dependent variable is blood pressure. Statistical tests in this study used the chi square test. The results obtained showed that there was a relationship between self-efficacy and motivation to prevent complications with the degree of hypertension in the elderly in the Working Area of ​​the Mukomuko City Health Center with a p value of 0.000 <α = 0.05. This research is useful for the community, especially the elderly with hypertension in order to be able to add insight and information about self-efficacy and motivation to prevent complications in order to control blood pressure.